PEMANFAATAN TEKNOLOGI DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR - Salsabela Ashlin; Julaiha Julaiha; Fatimah Azzahra; M. Hasbi Fadillah; Ahmad Suriansyah; Maimunah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of digital technology in elementary school teaching is becomingincreasingly important for increasing student learning interest. However, itsimplementation is not yet optimal and continues to face various challenges. Thepurpose of this study is to analyze the digital technology used, its impact on studentlearning interest, and the obstacles encountered in the learning process. Themethodology used included a literature review, evaluating relevant journals, books,and research reports. The results indicate that digital technologies such asinteractive learning videos, educational games, quiz applications, and onlinelearning platforms can increase student motivation, participation, and engagement.The visualization and interactivity of digital media encourage more active studentparticipation and facilitate understanding of learning content. However, variousobstacles also arise, such as limited teacher skills, inadequate infrastructure, andthe risk of disrupting student concentration. This study concludes that digitaltechnology can effectively increase student learning interest when supported byqualified teachers, adequate infrastructure, and appropriate learning strategies.